Initial characterisation of exosomes released by umbilical cord-derived mesenchymal stem cells and mature dendritic cells, under ‘Good Manufacturing Practice’ conditions - Hoang Huong Diem; Bui Thi Van Khanh; Hoang Thi My Nhung; Nguyen Thanh Liem; Than Thi Trang Uyen (Vietnam Journal of Science, Technology and Engineering, 2019)
Exosomes represent an important mode of intercellular communication and play key roles in many physiological and pathological processes. Exosomes have hitherto exhibited their capacity to modulate biological activities through their carrying of functional molecules such as proteins, lipids, and genetic materials. In the current study, we investigated exosomes released by mature dendritic cells (mDCs) and umbilical cord-derived mesenchymal stem cells (UCMSCs) under Good Manufacturing Practice (GMP) conditions. Ultracentrifugation was used to isolate and purify the exosomes. Additionally, a transmission electron microscope (TEM) and immunoblotting were used to characterise exosomal morphology and markers. The preliminary results showed that both mDCs and UCMSCs secreted exosomes into GMP culture media. Exosomes exhibited a cup-shaped morphology and showed positive for CD63. Additionally, no difference was observed between mDC-derived exosomes and UCMSC-derived exosomes regarding marker expression or morphology. This data indicates the potential for further development of GMP exosomes for clinical application.